INTERCULTURAL CONTACT IN ANDREA HIRATA’S EDENSOR - MALICHATIN, ILMIYATIN NUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key Words: Culture, Cultural Background, Intercultural Contact, Edensor.People with different cultural backgrounds have lead some research to reveal the phenomena of intercultural contact so many times. The revelation does not only exist in the formal research but also in some literary work, one of them is the story of a sojourner who faces new places which is appeared in Edensor. Through Ikal as the main character, this novel describes about the struggle of Ikal as a sojourner to face the various differences of each place he stays.This research applies Cultural Study since the novel concerns about cultures of each countries that are presented by Ikal through his narrations. This approach leads to use the theory of acculturation to explain deeply how Ikal as sojourner can accommodate himself to live in different countries. The identification of Ikal’s narration is used as the formal object to do the deep interpretation in this research. Therefore, the analysis of the research that deals about the intercultural contact among sojourner and new places can be seen clearly.The result of this research reveals that Ikal as a sojourner tries to notice and follow the native’ habits to show the politeness level when he notices the difference politeness level of his country, Indonesia, and another country. Therefore, his first hand of intercultural contact experience lead him to know each country’s politeness. Moreover, he tends to practice the native’s arts to do interaction with them after he discovers the difference of art’s tastes in every contries. The revelation of many kind of greetings which are difference from how Indonesian greet others is also a problem by Ikal that he has to practice those native’s greeting when he stays in native’s countries. As sojourner, the communication with the native people is important to do. However, Ikal tends to use the native’s native language to do communication when he can speak their native language, in contrary, he leaves that country when he can not speak the native language and the native can not speak Ikal’s language.